Korelasi kadar endocrine gland-derived vascular endothelial growth factor serum dengan tebal endometrium pada fertilitasi in vitro - TJ Avicenna; Ichwanul Adenin; Binarwan Halim (Fakultas Kedokteran USU, 2013)
introduction :To obtain numerous data concerning charecteristics, EGVEGF serum levels, endometrium thickness, and the correlation between EGVEGF serum levels and endometrium thickness on the day of oocytes aspiration in patients undergoing in vitro fertilization. Method : Analytic retrospective surveyResults : Twenty nine samples were obtained during the research which started from March 29th. Serum samples were obtained on the day of oocytes aspiration (ovum pick-up) conducted. The age group ranged from 31 years until 35 years old with the youngest subject aging 29 years and the oldest reaching 44 years old. The average age of patients undergoing in vitro fertilization was 34, 34 years with the standard deviation of 5.07. Patients undergoing in vitro fertilization were observed with primary infertility in 15 subjects (51.7%) whereas 14 patients undergoing the similar procedure were observed with secondary infertility. Sixteen patients undergoing invitro fertilization were found with a normoweight body mass index, 9 pateints were observed with an overweight value (31.0%), and 2 patients were observed with an underweight and obesity value (6.9%), respectively. Mean value of EGVEGF serum levels obtained from each subjects, reached 14.19 (SD 9.67) pg/mL with a minimal endometrium thickness of 6.5 mm and a maximal value of 14.3 mm. Correlation level tests of EGVEGF serum with a certain endometrium thickness level revealed no correlation value of -0.097 (rho = -0.097), with a P value of 0.617.Conclusion : No existance of correlation between EGVEGF serum levels with endometrium thickness on the day of oocytes aspiration in patients undergoing in vitro fertilization.Keywords : in vitro fertilization; endocrine gland-derived vascular endothelial growth factor (EGVEGF) serum levels; endometrial thickness